Mathematical model of the ichtyocenose with delays - Švitra, Donatas; Žemaitis, Giedrius (Lietuvos matematikos rinkinys, 2010)
This article describes the authors’ work the existing ecosystem in the Curonian Lagoon. Using the mathematical model of the ichtyocenose (1)–(2) is simulated the dynamics of the ichtyocenose in the Curonian Lagoon. It is done by using Runge–Kut IV method from this simulation program ModelMaker. The model numerical solutions of F1 - F8 are compared with the experimental data for the monitoring of fish. The dynamics is projected to the year 2016.